Technological Gap in Recommended Practices of Apple Cultivation in Kashmir Valley - Shah, Zahoor Ahmad; Dar, Mushtaq Ahmad; Dar, Eajaz Ahmad; Mir, Rufaida; Ali, Mohammed Tauseef (Indian Journal of Extension Education, 2022)
Apple is mainly cultivated in Kashmir valley, due to its well suited climatic conditions. The area under apple fruit has been increasing constantly, but the production as well as productivity has not improved to a satisfactory level. To notch up the goal of higher production and productivity of this important fruit in different regions of Kashmir valley, adoption of improved technologies plays an important role. A wide gap exists between the accessible technologies and its actual adoption by the apple growers, as reflected through the poor yield at the grower’s field. The study was conducted during 2019-20, with a view to determine the extent of technological gap between the recommended and actually adopted technologies by the apple growers in three districts of the Kashmir valley, selected purposively having maximum area under apple cultivation. A multistage sampling procedure was adopted for the study. It was found that the highest mean technological gap was found in district Budgam, followed by district Baramulla and the least gap existed in district Shopian. The overall mean technological gap index from all the three districts was found to be 63.08 per cent indicating need for scaling up extension efforts.
Keywords: Apple; Gap; Growers; Practices; Technology